Performance assessment in elite table tennis matches using the enhanced first offensive shot model - Liu, R.; Rothe, F.; Lames, M. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Technique and tactics are key elements in assessing table tennis performance and have been widely studied. However, most existing methods classify shots solely by sequence or shot number, overlooking the tactical attributes and their impact on rally outcomes. The First Offensive Shot (FOS) model attempted to address this issue but remained too coarse-grained. To overcome these limitations, this study introduces the Enhanced FOS model (EFOS), which integrates shot type and shot number into a more refined state-transition framework. This novel approach provides a more detailed representation of rally dynamics, enabling a deeper analysis of rally progression.